Risk Factors of Malnutrition among under Five Children Admitted in Kanti Children’s Hospital in Nepal - Karki, S.; Koirala, S.; Shrestha, S. (Kathmandu University Medical Journal, 2021)
Background World Health Organization (WHO) stated that malnutrition is a major global health and social problem from which many people are suffering, particularly children. Poor feeding and care practices, insufficient nutrient intake, high rate of infection and teenage pregnancy are the immediate causes of chronic malnutrition. Objective To identify the risk factors for malnutrition among under five children. Method A case control study was carried out among the mothers having under-5 years’ children who were admitted in the Kanti Children’s Hospital of Nepal from 1st August 2019 to 7th September 2020. Non-probability purposive sampling technique was used to select 50 children with malnutrition and 100 children without malnutrition matched on age, sex and setting. A structured interview was used to collect data from mothers of both cases and controls. Descriptive and inferential statistics were used to analyze the data. Result Present study reveals that 58% girl got marriage before 20 years. After confounders adjusted, mother’s age ≥ 20 years at marriage (OR: 2.74, 95% CI: 0.98-7.63. p=0.05), and mother’s age ≥ 20 years at child birth (OR: 7.74, 95% CI: 2.37-25.27. p=0.001), were significantly associated with having malnutrition among under five children. Similarly, accessibility of health facility (OR: 3.31, 95% CI: 1-10.94. p=0.05), fathers who completed master in education (OR: 0.08, 95% CI: 0.01-0.88. p=0.04), children who lived in joint family (OR: 0.25, 95% CI: 0.07-0.86. p=0.03), child < 2.5 kg at birth (OR: 0.18, 95% CI: 0.05-0.62. p=0.01), and second and third or above in order (OR: 0.09, 95% CI: 0.01-1.04. p=0.05) had significantly less chance of having malnutrition. Children’s whose birth interval was 2-3 years were significantly (OR: 9.74, 95% CI: 1.16-82.23. p=0.04) associated with the occurrence of malnutrition. Children who had suffered from multiple co-morbidities in last one year were (OR: 4.55, 95% CI: 0.48-43.03. p=0.18) more chance of having malnutrition. Likewise, the mothers who feed colostrum to their child had (OR: 2.28, 95% CI: 0.52- 9.26. p=0.29) almost two-fold less chance of having malnutrition. Mothers who had done exclusive breast feeding ≥ 4 months had (OR: 40.55, 95% CI: 3.35-1.490.92. p=0.008) significantly associated with having malnutrition. Conclusion Low education status of father, living in single family, exclusive breast feeding ≥ 4 months, lack of balance diet were significant risk factors of malnutrition. Based on finding, reliable longitudinal studies, interventions and program to educate parent for prevention of malnutrition are necessary in future.